2020
DOI: 10.1108/nfs-10-2019-0318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrocolloids on quality characteristics, functionality and microstructure of spinach puree–enriched instant noodles

Abstract: Purpose Noodles are good vehicles for the enrichment and can be enriched with vegetable purees. However, this enrichment can alter quality attributes of noodles with resultant effect on its sensorial attributes. The purpose of this paper is to study the effect of addition of different hydrocolloids on the microstructural and quality characteristics of instant noodles enriched with spinach puree. Design/methodology/approach Preliminary trials were carried out for the standardization level of addition of spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…The addition of gum in pasta formulation at different levels showed no significant effect on pasta color. Similar effect of hydrocolloids on color characteristics of developed noodles was observed by Shere et al (2020) Color values of cooked and uncooked pasta were significantly different which could be related to the leaching of pigments on cooking.…”
Section: Color Characteristics Of Pastasupporting
confidence: 67%
“…The addition of gum in pasta formulation at different levels showed no significant effect on pasta color. Similar effect of hydrocolloids on color characteristics of developed noodles was observed by Shere et al (2020) Color values of cooked and uncooked pasta were significantly different which could be related to the leaching of pigments on cooking.…”
Section: Color Characteristics Of Pastasupporting
confidence: 67%
“…The swelling index of the product and control were 0.9 and 1.0, respectively. The swelling index of range 1.29–1.89 was reported by Shere et al (2020) for spinach noodles incorporated with CMC and guar gum. The swelling index factor showed that the control expanded with 5.3% more than the product when cooked.…”
Section: Resultsmentioning
confidence: 88%
“…Manthey and Schorno (2002) report the value of 10.8 min for whole wheat spaghetti. Shere et al (2020) reported the cooking time values of 5.2–8.5 min for spinach noodles incorporated with carboxymethyl cellulose (CMC) and guar gum. The swelling index of the product and control were 0.9 and 1.0, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations